Жерсіндіруге бейімделу кезінде қанның морфологиялық жəне биохимиялық өзгерістері - Мырзаханов, Н.М.; Айткенова, А.А.; Рахимжанова, А.С. (ҚарМУ баспасы, 2010)
В статье характеризуются некоторые селекционные, физиологические и биохимические показатели крови новой породы овец «Байыс». Авторами определены содержание эритроцитов, лейкоцитов, гемоглобина, лейкоцитарная формула, концентрация сахара и ферментов АлАТ и АсАТ у животных в момент акклиматизации и через год после адаптации. В статье приводятся материалы о положительном направлении акклиматизационной адаптации животных. This article some characterization of the selection, physiology and biochemi index of the new breed «Bays» by acclimation adaptation of the mountain-steppe region of the Karkaralinsk. Authors of the definition quantity of eritrocyte, leukocyte, hemoglobine, leukocyts formule, sugar, AcAT and AsAT ferments of the blood sheepe before and after acclimation adaption. This article let us materials of the positive towards acclimation adaptation of the sheeps, characterize some of breeding, physiological and biochemical blood parameters of a new breed of sheep